2014
DOI: 10.18052/www.scipress.com/ilcpa.39.78
|View full text |Cite
|
Sign up to set email alerts
|

Significant Influence of Annealing Temperature and Thickness of Electrode on Energy Conversion Efficiency of Dye Sensitized Solar Cell: Effect of Catalyst

Abstract: Dye sensitized solar cell (DSSC) shows great promise as an alternative to conventional p-n junction solar cells due to their low fabrication cost and reasonably high efficiency. DSSC was assembled by using natural dye extracted from red amaranth (Amaranthus Gangeticus) as a sensitizer and different catalysts for counter electrode were applied for maximum energy conversion efficiency. Annealing temperature and thickness of electrode were also investigated and optimized. Catalyst, annealing temperature and thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Then, six types of counter electrodes have been prepared by using these different forms of carbon according to our previous study [20]. Here, the conductive side of one ITO coated glass was placed over the tip of a candle flame for 30 s to get a dark shade of carbon for one of the counter electrodes [19].…”
Section: Preparation Of Counter Electrodementioning
confidence: 99%
“…Then, six types of counter electrodes have been prepared by using these different forms of carbon according to our previous study [20]. Here, the conductive side of one ITO coated glass was placed over the tip of a candle flame for 30 s to get a dark shade of carbon for one of the counter electrodes [19].…”
Section: Preparation Of Counter Electrodementioning
confidence: 99%
“…Meanwhile, there are still few studies investigating the influence of the TiO2 layer thickness. Characterization is required to determine the ability of TiO2 to bind to the dye and then affects the power output produced [37,38]. Therefore, the objective of this research is to utilize red dragon fruit as a dye base for DSSC manufacture and to determine the effect of TiO2 thickness on DSSC performance by varying its thickness.…”
Section: Introductionmentioning
confidence: 99%
“…DSSCs became more popular among other generations of solar cells in the photovoltaic research world when O'Regan and Gräetzel reported an efficiency (η) of 7.1% using inorganic Ruthenium (II) dye as a sensitizer for the fabrication of DSSCs [2]. This paves way for several investigations to be conducted using a different technique to improve the DSSC performance [3][4][5][6][7]. Compared to other categories of solar cell generations [1], DSSCs are low-cost, more eco-friendly photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%